PERAN UMKM DALAM MENANGGULANGI KEMISKINAN DI PROVINSI JAWA TIMUR - Fajrin Novi Anugerah; Ida Nuraini (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of the number of MSMEs and labors of MSMEs to the poverty of East Java during the period 2017-2018. The variables dependent used in this study is the number of poverty in East Java, while the independent variable are number of MSMEs and labor of MSMEs in East Java This study used panel data regression analysis techniques. The selected model in this study by Chow Test and Hausman Test is fixed effect method (FEM). The data used in this research is secondary data. The results of this study indicate a Prob (F-statistic) value of 0.000000. It can be said that simultaneously the variable number of MSMEs and labor of MSMEs have an effect on poverty of East Java. A value Determinasi Coeficient (R2) is 65.65% Panel data regression calculation results in this study indicate that a variable number of MSMEs with t-Statistics amounted to -7.677828 and probability amounted to 0,0000 means variable number of MSMEs have a negative influence and significant impact on poverty, while the variable labor MSMEs with t-Statistics amounted to -0.971239 and probability amounted to 0,3379 means variable number labor of MSMEs has no effect on poverty. Partially, the variable Number of MSMEs and number labor of MSMEs with F-Probability amounted to 0.000000 so that it can be concluded that the two variables have a positive and significant effect on poverty